O papel das Atividades de Vida Diária no processo de autonomização das pessoas portadoras de deficiência: https://doi.org/10.53809/TS_ISS_2023_n.4_79-91 ("Temas Sociais" Journal, 2023)
The conceptual model of disability is based on the expression of limitations of a person's individual functioning in a social context that clearly represents a disadvantage for the subject himself. The importance of social inclusion and the promotion of the autonomy of people with intellectual disabilities are two crucial aspects of the intervention and, at the same time, they are conceptually interconnected. This synergy makes it possible to understand the connection between both and the importance that each one represents in the lives of people with intellectual disabilities. In this way, generically, inclusion confers the notion of belonging, equality and responsibility towards the other elements and, in turn, autonomy confers freedom of choice and the satisfaction of a personal desire. This conceptual exploration work has as its central objective, to emphasize the importance of the existence of integrated intervention in terms of maintenance and training of Activities of Daily Living and their constituents in people with intellectual disabilities. It is concluded that the achievement of overcoming the difficulties of individuals with intellectual disabilities integrates individual involvement supported by their personal networks and the mobilization of society.